Australians' experiences of COVID-19 during the early months of the crisis: A qualitative interview study - Lupton, Deborah; Lewis, Sophie (Frontiers in Public Health, 2023)
Introduction The COVID-19 crisis has wrought major changes to people's lives across the globe since the beginning of the outbreak in early 2020. The "Australians' Experiences of COVID-19” qualitative descriptive study was established to explore how Australians from different geographical areas and social groups experienced the COVID-19 crisis. Methods Three sets of semi-structured interviews, each with a diverse group of 40 adults across Australia, were completed between 2020 and 2022. This article reports findings from the first set of interviews, conducted by telephone in mid-2020. Results The participants discussed their experiences of living through this period, which was characterized by strong public health measures to contain the spread of COVID, including a national lockdown and border closures. Interview fieldnotes and verbatim transcripts were used to conduct an interpretive thematic analysis. The analysis is structured around the following five themes covering the quotidian and affective aspects of participants' lives in the early months of the COVID crisis: “disruption to routines;” “habituating to preventive measures;” “social isolation and loneliness;” “changes to work and education;” and “little change to life.” A sixth theme concerns how participants responded to our question about what they imagined their lives would be like after the pandemic: “imagining post-COVID life.” Discussion The crisis affected participants' experience of daily life variously according to such factors as their social circumstances and obligations as well as their histories of illness, making visible some of the unequal social and economic effects of the pandemic across different genders, ages, localities and socioeconomic groups. Our participants fell into three roughly equal groups: (i) those who found the lockdown and associated restrictions very difficult; (ii) those who reported feeling barely affected by these conditions; and (iii) those who found benefits to the “slowing down” of life during this period.